Unleashing anti-tumor immunity: Targeting the autophagy-related protein VPS34 to enhance STING agonist-based therapy - Elisabetta Bartolini; Kris Van Moer; Bassam Janji (Autophagy Reports)
The release of CCL5 and CXCL10 is essential for recruiting cytotoxic immune cells into the tumor microenvironment and enhancing the efficacy of cancer immunotherapy. Type I IFNs, particularly IFNβ, activate signaling pathways that induce the expression of these chemokines. In our recent study, we explored the impact and underlying mechanisms of inhibiting the kinase activity of VPS34, a key lipid kinase in the autophagy/endosomal trafficking system, on the expression of CCL5 and CXCL10 in preclinical cancer mouse models. Using NanoString gene expression technology, we analyzed tumors from mice treated with the VPS34 inhibitor SB02024 and demonstrated that the expression of CCL5 and CXCL10 is increased through a cGAS-STING-dependent mechanism within cancer cells. In vitro, both pharmacological inhibition and genetic targeting of VPS34 enhance cGAS-STING-mediated expression and secretion of CCL5 and CXCL10 across various tumor cell types. In vivo, treatment with the VPS34 inhibitor SB02024 enhances the positive effects of the STING agonist ADU-S100 in melanoma tumor-bearing mice. Thus, our study suggests that VPS34 inhibitors could be used to enhance STING-based anticancer therapies.Abbreviations CCL5 (C-C motif chemokine 5); CXCL10 (C-X-C motif chemokine 10); IFN (interferon); VPS34 (vacuolar protein sorting 34); cGAS (cyclic GMP-AMP Synthase); STING (stimulator of interferon genes protein); cGAMP (2′3′-cyclic guanosine monophosphate–adenosine monophosphate).